Flux-enhanced reduced graphene oxide (rGO)/PVDF nanofibrous membrane distillation membranes for the removal of boron from geothermal water - Eryildiz, Bahriye; Ozbey-Unal, Bahar; Gezmis-Yavuz, Elifnur; Koseoglu-Imer, Derya Y.; Keskinler, Bülent; Koyuncu, Ismail (Elsevier, 2021)
In this work, fabrication of PVDF nanofiber membrane with reduced graphene oxide (rGO) using electrospinning technique has been carried out to improve AGMD performance. Membrane morphology and different membrane characteristics such as contact angle, thickness, liquid entry pressure (LEP), young module, scanning electron microscopy (SEM) and surface roughness of membrane were analyzed for the characterization of hydrophobic nanofiber membranes. Firstly, rGO/PVDF membranes with different rGO concentrations were produced using the electrospinning method. All fabricated rGO/PVDF membranes were characterized and used in the AGMD system for the treatment of saline water. Secondly, the selected optimum membrane according to characterization and filtration results was used in the AGMD system for the treatment of synthetic and real geothermal water. Results showed that all rGO membranes exhibit higher permeate water flux and salt rejection, lower permeate boron or salt concentration than pure PVDF membrane. In real geothermal water experiments, rGO/PVDF membrane (0.039 wt%) were improved permeate water flux from 19.20 to 30 L/m2.h, boron rejection from 96.89% to 98.16%. Also, permeate boron concentration was decreased using rGO/PVDF membrane (0.039 wt%) from 0.305 mg/L to 0.226 mg/L. As a result, fabricated rGO/PVDF membranes were achieved to the enhanced performance of the AGMD system.
Keywords: Reduced graphene oxide; Air gap membrane distillation; Removal of boron; Geothermal water; Nanofiber membrane